Does Pain Catastrophizing and Distress Intolerance Mediate the Relationship Between PTSD and Prescribed Opioid Misuse in People With Chronic Noncancer Pain? - López-Martínez, Alicia Eva; Sainero-Tirado, Gloria; Esteve-Zarazaga, Rosa; Reyes-Pérez, Ángela; Ruiz-Párraga, Gema Teresa; De la Vega, Rocío; Serrano-Ibáñez, Elena Rocío; Ramírez-Maestre, María del Carmen (My University, 2023)
Objective: There is an ongoing debate on the use of long-term high-dose medically prescribed opioid analgesics for patients with chronic noncancer pain. Such use is elevated when there is comorbid pain and PTSD, which is quite prevalent. Therefore, it is relevant to investigate the psychological variables that may explain opioid misuse in this population. The purpose of this study was to examine the interaction effect of PTSD severity, distress intolerance, and pain catastrophizing on prescribed opioid misuse in chronic noncancer pain patients. Method: A total of 168 participants (M age = 60 years, 74% women) were assessed regarding opioid medication, pain intensity, traumatic psychological events, PTSD, distress intolerance, pain catastrophizing, and current opioid misuse. Results: Groups were formed according to the level of PTSD severity (no symptoms, moderate symptoms, and severe symptoms). Significant differences were found between the groups in pain intensity, catastrophizing, distress intolerance, and opioid misuse. The severe-symptoms group had the highest scores on all variables. There were no between-group differences in the prescribed medication. Mediation analysis showed that the relationship between PTSD severity and opioid misuse was completely and independently mediated by distress intolerance and pain catastrophizing. Conclusions: Distress intolerance and pain catastrophizing may be theoretically and clinically relevant constructs in understanding the motivation for opioid misuse in people with concurrent chronic noncancer pain and PTSD.
Última versión de borrador en PDF
Keywords: Dolor; Opiáceos; Estrés (Psicología); Chronic noncancer pain; PTSD; Opioid misuse; Distress intolerance; Catastrophizing